Preliminary report on the soundings at tepe damghani sabzevar, spring 2008 - Fouache, Eric (2014)
A season of archaeological sounding at Tepe Damghani and survey of the surrounding area was carried out by a joint Irano-French expedition in the Spring of 2008. A multidisciplinary approach was adopted consisting of archaeological, geomorphological, archaeobotanical, archaeozoological, and anthropological studies for better understanding of the different aspects of the Bronze and Iron Age cultures at the site. Data-gathering was made possible through a small trial trench (Tr. 1) and cleaning of a large section which was exposed by road construction. Archaeological analysis of the materials from a sounding at Tepe Damghani and the survey of the neighbouring sites (Tepe Ferizi and Mirabad sites) show strong cultural links with Central Asia from the late Chalcolithic to the late Bronze Age. Iron Age material can only be found in the plough zone, but not in situ. Typological analysis of pottery, confirmed by various radiocarbon dates, suggest that the main occupation at Tr. 1 belongs to a period contemporary with Namazga IV (Early Bronze Age) in the Central Asian chronology. The discovery of various chert and ophiolitic artifacts indicate exploitation of local resources and the presence of chipping industry at the site during the Bronze Age, but no workshops were uncovered. Study of animal bones, wood charcoals, as well as charred seeds and fruit remains has provided us with invaluable information on subsistence pattern and plant economy of the ancient inhabitants of Tepe Damghani and allows us to answer various questions regarding the ancient water management and the exploitation and use of local faunal and floral resources.